2017
DOI: 10.1007/s11581-017-1979-z
|View full text |Cite
|
Sign up to set email alerts
|

Ionic conductivity improvement in poly (propylene) carbonate-based gel polymer electrolytes using 1-butyl-3-methylimidazolium iodide (BmimI) ionic liquid for dye-sensitized solar cell application

Abstract: Gel polymer electrolytes (GPEs) are prepared by mixing poly (propylene) carbonate (PPC) with various weight percentages of 1-butyl-3-methylimidazolium iodide (BmimI) ionic liquid. The GPEs consist of PPC host polymer, NaI iodide salt, ethylene carbonate (EC), propylene carbonate (PC), BmimI ionic liquid, and iodine (I 2 ). The optimum BmimI ionic liquid content was found to be 60 wt% with respect to the wt% of PPC polymer with the highest ionic conductivity of 4.79 × 10 −3 S cm −1 . Temperature-dependent ionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…As seen in both Figure 10a,b, there is an increment in overall solar cell efficiency for binary IL‐based GPE system compared to a single IL‐based GPE system. The ionic conductivity of single/binary IL‐based GPE has a clear correlation with J sc and the overall power efficiency of DSSCs 28 . From the comparison of the single IL system and binary IL system, we see the increment from 2.78% reaching to maximum efficiency of 7.61% and 7.80% for system 1 (EMIM‐4) and system 2 (BMIM‐3), respectively.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…As seen in both Figure 10a,b, there is an increment in overall solar cell efficiency for binary IL‐based GPE system compared to a single IL‐based GPE system. The ionic conductivity of single/binary IL‐based GPE has a clear correlation with J sc and the overall power efficiency of DSSCs 28 . From the comparison of the single IL system and binary IL system, we see the increment from 2.78% reaching to maximum efficiency of 7.61% and 7.80% for system 1 (EMIM‐4) and system 2 (BMIM‐3), respectively.…”
Section: Resultsmentioning
confidence: 83%
“…The Arrhenius model is the relationship between ionic conductivity, activation energy, and temperature. It is stated in the following Equation () 28 : σ=σ0eEaKnormalbT where σ is ionic conductivity, σo pre‐exponential constant, E a is the activation energy (eV), K b is Boltzmann constant, and T is the absolute temperature (K). The activation energy can be obtained by using the slope of the graph 10 .…”
Section: Resultsmentioning
confidence: 99%
“…As the substrate used in the XRD test is SiO 2 , the diffraction peak at 2θ = 10 • -30 • is attributed to amorphous SiO 2 . In the XRD result before Soxhlet extraction, the diffraction peaks at 13 • and 26 • belong to BmimI crystal [37]. There is no diffraction peak of Au 0 in the sample after leaching, indicating that Au 0 has all been oxidized to gold ions and loaded in the ionic liquid phase.…”
Section: Extraction Gold From Spent Catalystmentioning
confidence: 98%
“…When the current space missions are targeting the ocean worlds where an icy shell covers the surface of the planets (e.g., Europa, Enceladus, and Titan), the development of an electrolyte that can adapt to the extreme temperature conditions rises up to a necessity and a priority. Electrolytes that consist of [BMIM]­[I] have been widely studied, , but their behaviors and limits of performance at low temperatures are still unrevealed. Nickerson et al reported that the addition of water will reduce the viscosity of [BMIM]­[I] in the binary mixture with the focus on their properties at room temperature .…”
Section: Introductionmentioning
confidence: 99%